Analisis Lingkungan Fisik Rumah pada Kejadian ISPA (Infeksi Saluran Pernapasan Akut) di Wilayah Kerja Puskesmas Betungan Kota Bengkulu - Merdilah, Salta Niya; Sari, Aplina Kartika (Jurnal Sanitasi Profesional Indonesia, 2025)
Acute Respiratory Infections (ARI) remain a leading cause of morbidity and mortality among children, especially in developing countries. Poor physical housing conditions such as inadequate ventilation, low lighting, extreme temperatures, and high humidity are major risk factors for ARI. This study aimed to analyze the physical environment of homes of ARI patients in the Betungan Health Center area. A descriptive design was employed through direct observation and measurements of 95 houses.The results revealed that 50.5% of homes had inadequate ventilation, 56.9% lacked proper lighting, 54.8% had improper temperature levels, and 55.8% had high humidity. These findings indicate that most ARI-affected homes did not meet environmental health standards and may contribute to increased infection risk. Therefore, improving the physical conditions of housing is essential to reduce the incidence of ARI.